GABAA receptors in the basal forebrain mediates emergence from propofol anaesthesia in rats. (3rd August 2022) - Liu, Chengxi; Shi, Fu; Fu, Bao; Luo, Tianyuan; Zhang, Lin; Zhang, Yu; Zhang, Yi; Yu, Shouyang; Yu, Tian
Abstract: Purpose: The aim of the current study was to explore the role of the basal forebrain (BF) in propofol anaesthesia. Methods: In the present study, we observed the neural activities of the BF during propofol anaesthesia using calcium fibre photometry recording. Subsequently, ibotenic acid was injected into the BF to verify the role of the BF in propofol anaesthesia. Finally, to test whether GABAA receptors in the BF were involved in modulating propofol anaesthesia, muscimol (GABAA receptor agonist) and gabazine (GABAA receptor antagonist) were microinjected into the BF. Cortical electroencephalogram (EEG), time to loss of righting reflex (LORR), and recovery of righting reflex (RORR) under propofol anaesthesia were recorded and analysed. Results: The activity of BF neurons was inhibited during induction of propofol anaesthesia and activated during emergence from propofol anaesthesia. In addition, non-specifical lesion of BF neurons significantly prolonged the time to RORR and increased delta power in the frontal cortex under propofol anaesthesia. Next, microinjection of muscimol into the BF delayed emergence from propofol anaesthesia, increased delta power of the frontal cortex, and decreased gamma power under propofol anaesthesia. Conversely, infusion of gabazine accelerated emergence times and decreased EEG delta power. Conclusions: The basal forebrain is involved in modulating frontal cortex delta activity and emergence from propofol anaesthesia. Additionally, the GABAA receptors in the basal forebrain are involved in regulating emergence propofol anaesthesia.